{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

math-2011-note9

# math-2011-note9 - Theorem 41(Thm 30.5 p.828 Let f R 1 → R...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Theorem 41 (Thm 30.5, p.828) . Let f : R 1 → R 1 be a C 2 function. For any point a < b ∈ R 1 , there is a point c ∈ ( a , b ) such that f ( b ) = f ( a ) + f prime ( a )( b- a ) + 1 2 f primeprime ( c )( b- a ) 2 . Proof. Define M = 2 ( b- a ) 2 bracketleftbig f ( b )- f ( a )- f prime ( a )( b- a ) bracketrightbig . Suppose that f primeprime ( x ) negationslash = M for all x ∈ ( a , b ) . Then either f primeprime ( x ) > M ∀ x ∈ ( a , b ) or f primeprime ( x ) < M ∀ x ∈ ( a , b ) . Suppose that f primeprime ( x ) > M ∀ x ∈ ( a , b ) . Then, we have f prime ( t )- f prime ( a ) = integraldisplay t a f primeprime ( x ) dx > integraldisplay t a M dt = M ( t- a ) , ∀ t ∈ ( a , b ) Hence, f prime ( t ) > f prime ( a )+ M ( t- a ) ∀ t ∈ ( a , b ) . So we have f ( b )- f ( a ) = integraldisplay b a f prime ( t ) dt > f prime ( a )( b- a )+ M integraldisplay b a ( t- a ) dt = f prime ( a )( b- a )+ M ( b- a ) 2 2 , a contradiction to the definition of M , which shows that it cannot be the case that...
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

math-2011-note9 - Theorem 41(Thm 30.5 p.828 Let f R 1 → R...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online